Table 1_Independent component analysis of resting-state fMRI identifies regions associated with seizure freedom after laser interstitial thermal therapy for temporal lobe epilepsy.docx - Mahdi Alizadeh (13255536) (2025)
Objective Temporal lobe epilepsy (TLE) is a common form of drug-resistant epilepsy often treated with surgical interventions, including laser interstitial thermal therapy (LITT). However, patient-specific factors influencing LITT outcomes remain unclear. This retrospective study aimed to identify pre-operative resting-state functional MRI (rs-fMRI) patterns associated with seizure freedom following LITT in mesial TLE. Methods We analyzed rs-fMRI data from 28 patients with mesial TLE who underwent LITT, classifying them into seizure-free (SF) and not seizure-free (NSF) groups based on 12-month post-operative outcomes. Independent component analysis (ICA) was used to identify subject-specific brain networks, and generalized linear models (GLM) were employed to assess associations between pre-operative spatial patterns of ICA-derived functional connectivity (FC) and surgical outcomes, controlling for clinical variables. Results Significant differences in brain ICA-derived FC patterns were observed between SF and NSF groups, with SF exhibiting more locally distributed ICA-derived FC patterns around the mesial temporal lobe, including the posterior orbitofrontal cortex (OFC) and anterior parahippocampal gyrus (PHG). In contrast, NSF demonstrated more diffusely distributed ICA-derived FC patterns encompassing the insula and thalami. Significance These findings highlight the potential of pre-operative rs-fMRI as a prognostic tool for identifying TLE patients more likely to benefit from LITT. Further validation in larger cohorts is warranted to confirm these results and optimize patient selection for surgical interventions.